Interstitial needles versus intracavitary applicators only for locally advanced cervical cancer: results from real-life dosimetric comparisons - Cordoba, Abel; Gesta, Estelle; Escande, Alexandre; Noeuveglise, Alexandra; Cayez, Romain; Halty, Adrien; Ladjimi, Mohamed Tahar; Narducci, Fabrice; Hudry, Delphine; Martinez Gomez, Carlos; Cordoba, Sofia; Le Deley, Marie-Cécile; et al. (Frontiers in Oncology, 2024)
Background and Purpose: Image-guided adapted brachytherapy (IGABT) is superior to other radiotherapy techniques in the treatment of locally advanced cervical cancer (LACC). We aimed to investigate the benefit of interstitial needles (IN) for a combined intracavitary/interstitial (IC/IS) approach using IGABT over the intracavitary approach (IC) alone in patients with LACC after concomitant external beam radiotherapy (EBRT) and chemotherapy.We included consecutive patients with LACC who were treated with IC/IS IGABT after radiochemotherapy (RCT) in our retrospective, observational study. Dosimetric gain and sparing of organs at risk (OAR) were investigated by comparing the IC/IS IGABT plan with a simulated plan without needle use (IC IGABT plan) and the impact of other clinical factors on the benefit of IC/IS IGABT.Results: Ninety-nine patients were analyzed, with a mean EBRT dose of 45.5 ± 1.7 Gy; 97 patients received concurrent chemotherapy. A significant increase in median D90% High Risk Clinical target volume (HR-CTV) was found for IC/IS (82.8 Gy) vs IC (76.2 Gy) (p < 10 -4 ). A significant decrease of the delivered dose for all OAR was found for IC/IS vs IC for median D2cc to the bladder (77.2 Gy), rectum (68 Gy), sigmoid (53.2 Gy), and small bowel (47 Gy) (all p < 10 -4 ).Conclusions: HR-CTV coverage was higher with IC/IS IGABT than with IC IGABT, with lower doses to the OAR in patients managed for LACC after RCT. Interstitial brachytherapy in the management of LACC after radiotherapy provides better coverage of the target volumes, this could contribute to better local control and improved survival of patients.